Religious Habituation Program Management to Shape Student Discipline in Islamic Junior Secondary Schools - anita zahra; Ilham Fahmi; Saprialman Saprialman (UIN Siber Syekh Nurjati Cirebon, 2026)
This article aims to analyze the management of religious habituation programs in shaping student discipline in Islamic junior secondary schools. The study uses a literature review method by examining journal articles, academic books, and educational regulations related to Islamic educational management, religious habituation, madrasa culture, and student discipline. The data were analyzed through source reduction, thematic classification, content synthesis, and conceptual conclusion drawing. The findings indicate that religious habituation contributes to student discipline because religious activities train regularity, punctuality, responsibility, obedience to school rules, and awareness of obligations. The program becomes more effective when it is managed through planning, organizing, implementation, supervision, and evaluation. Forms of activities include collective prayer, Qur'an recitation, dhuha prayer, congregational prayer, greeting culture, charity, clean culture, and moral guidance. This study affirms that the success of religious habituation requires the commitment of the madrasa principal, teacher role modeling, student participation, parental support, and continuous evaluation.Keywords : Islamic educational management, religious habituation, student discipline, Islamic junior secondary school, literature review